2016
DOI: 10.1371/journal.pone.0168978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antifouling Biocides on Molecular and Biochemical Defense System in the Gill of the Pacific Oyster Crassostrea gigas

Abstract: Antifouling biocides such as organotin compounds and their alternatives are potent toxicants in marine ecosystems. In this study, we employed several molecular and biochemical response systems of the Pacific oyster Crassostrea gigas to understand a potential mode of action of antifouling biocides (i.e. tributyltin (TBT), diuron and irgarol) after exposure to different concentrations (0.01, 0.1, and 1 μg L-1) for 96 h. As a result, all the three antifouling biocides strongly induced the antioxidant defense syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…For instance, Zhang et al (2015b) observed increased levels of several sHsps in C. gigas exposed to thermal stress, whilst no alteration in the same proteins were observed in oysters exposed to hypoosmotic stress or aerial exposure. Park et al (2016) also observed differential expression profiles of the gene expression of several Hsp families in response to different biofouling agents. Therefore, our results showing decreased expression of α-crystallin b could result from concerted regulation of Hsps in response to As exposure.…”
Section: Crassostrea Angulatamentioning
confidence: 82%
“…For instance, Zhang et al (2015b) observed increased levels of several sHsps in C. gigas exposed to thermal stress, whilst no alteration in the same proteins were observed in oysters exposed to hypoosmotic stress or aerial exposure. Park et al (2016) also observed differential expression profiles of the gene expression of several Hsp families in response to different biofouling agents. Therefore, our results showing decreased expression of α-crystallin b could result from concerted regulation of Hsps in response to As exposure.…”
Section: Crassostrea Angulatamentioning
confidence: 82%
“…So far, organotins are the most effective methods of biofouling control; however, these chemicals are toxic to aquatic environments ( Yebra, Kiil & Dam-Johansen, 2004 ). The use of such toxic biocides presents environmental concerns involving anomalies in non-target organisms that include shell malformation in bivalves, depletion of oyster population, imposex in gastropods, and others ( Park et al, 2016 ). TBT has been labeled as the most lethal substance to have been deliberately introduced in to the marine environment by man ( Park et al, 2016 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…The use of such toxic biocides presents environmental concerns involving anomalies in non-target organisms that include shell malformation in bivalves, depletion of oyster population, imposex in gastropods, and others ( Park et al, 2016 ). TBT has been labeled as the most lethal substance to have been deliberately introduced in to the marine environment by man ( Park et al, 2016 ). In general, the use of such toxins in marine environments poses a real threat to the marine biota ( Fleming et al, 2006 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Since mollusks and crustaceans are important fisheries worldwide, many studies on OT accumulation and toxicity were developed in these animals ( 16 , 17 ). Marine bivalves (mussels, clams, and oysters) tend to accumulate higher OT levels than fishes or crustaceans ( 13 , 14 , 16 ). Tributyltin (TBT) and triphenyltin, the most toxic forms of OTs, are well-recognized endocrine-disrupting chemicals of mollusks causing imposex or masculinization of females in more than 200 species ( 4 , 13 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Marine bivalves (mussels, clams, and oysters) tend to accumulate higher OT levels than fishes or crustaceans ( 13 , 14 , 16 ). Tributyltin (TBT) and triphenyltin, the most toxic forms of OTs, are well-recognized endocrine-disrupting chemicals of mollusks causing imposex or masculinization of females in more than 200 species ( 4 , 13 , 18 , 19 ). Fishes and marine mammals can be contaminated either by drinking or by ingesting OTs-contaminated invertebrates.…”
Section: Introductionmentioning
confidence: 99%